Evaluation of Eight-Item Vancomycin Prescribing Confidence Questionnaire Among Junior Doctors - Liu, Lu; Jiang, Zhehan; Xie, Ana; Wang, Weimin (Frontiers in Medicine, 2021)
Assessing the preparedness of junior doctors to use vancomycin is important in medical education. Preparedness is typically evaluated by self-reported confidence surveys. An 8-item vancomycin prescribing confidence questionnaire was developed, piloted, and evaluated. The questionnaire responses were collected from 195 junior doctors and a series of statistical techniques, such as principal component analysis and confirmatory factor analysis, were implemented to examine the validity and reliability. The principal component analysis supported a one-factor structure, which was fed into a confirmatory factor analysis model resulting in a good fit (CFI=0.99, TLI=0.99, RMSEA=0.08, SRMR=0.04). Ordinal-based α was 0.95 and various ωs were all above 0.93, respectively, indicating a high-reliability level. The questionnaire responses were further proved to be robust to extreme response patterns via item response tree modelling. Jonckheere-Terpstrata test results (z = 6.5237, p = 3.429e-11) showed that vancomycin prescribing confidence differed based on the experience in order (i.e., four ordinal independent groups: "≤ 10 times ", "11-20 times", "21-30 times" and "≥ 31 times") and therefore provided external validity evidence for the questionnaire. The questionnaire is valid and reliable such that teaching hospitals can consider using it to assess junior doctors’ vancomycin prescribing confidence.